The Challenges of Afghanistan and Iraq Veterans’ Transition from Military to Civilian Life and Approaches to Reconnection - Ahern, Jennifer; Worthen, Miranda; Masters, Jackson; Lippman, Sheri A.; Ozer, Emily J.; Moos, Rudolf (PLOS ONE, 2015)
Afghanistan and Iraq veterans experienced traumas during deployment, and disrupted connections with friends and family. In this context, it is critical to understand the nature of veterans’ transition to civilian life, the challenges navigated, and approaches to reconnection. We investigated these issues in a qualitative study, framed by homecoming theory, that comprised in-depth interviews with 24 veterans. Using an inductive thematic analysis approach, we developed three overarching themes. Military as family explored how many veterans experienced the military environment as a “family” that took care of them and provided structure. Normal is alien encompassed many veterans experiences of disconnection from people at home, lack of support from institutions, lack of structure, and loss of purpose upon return to civilian life. Searching for a new normal included strategies and supports veterans found to reconnect in the face of these challenges. A veteran who had successfully transitioned and provided support and advice as a peer navigator was frequently discussed as a key resource. A minority of respondents—those who were mistreated by the military system, women veterans, and veterans recovering from substance abuse problems—were less able to access peer support. Other reconnection strategies included becoming an ambassador to the military experience, and knowing transition challenges would ease with time. Results were consistent with and are discussed in the context of homecoming theory and social climate theory. Social support is known to be protective for veterans, but our findings add the nuance of substantial obstacles veterans face in locating and accessing support, due to disconnection and unsupportive institutions. Larger scale work is needed to better understand how to foster peer connection, build reconnection with family, and engage the broader community to understand and support veterans; interventions to support reconnection for veterans should be developed.